The Imperative Speech-act and Language Politeness for Government Officers of South Sulawesi in THE NEW SULSEL Book - Yusriadi Yusriadi; Lukman Lukman; Asriani Abbas (Hasanuddin University, 2021)
This research aims to (1) classify the forms of imperative speech of government officials of South Sulawesi Province, and (2) explain the strategy of politeness of imperative speech of government officials of South Sulawesi Province in The New Sulsel Book. The type of research used is descriptive qualitative which describes the facts that are empirically present in the speakers. The results showed that the form of imperative speech acts of government officials of South Sulawesi Province were declarative, interrogative, and optative. In terms of this form, the tendency of official imperative speech is more dominant declaratively and optatively, which means that the imperative element is implied. This can not be separated from the principle of local culture 3S (Sipakatau, Sipakalebbi, Sipakainge) which means to humanize, respect and remind each other. Furthermore, the imperative speech politeness strategies of South Sulawesi Provincial government officials include direct politeness, indirect politeness, positive politeness, and negative politeness. In this strategy, the speech of officials is more likely to be a positive politeness strategy which means that officials in the South Sulawesi provincial government are very polite in conveying imperative speech or orders. This condition can have an impact on not maximizing the command message delivered so that it makes the partner or interlocutor not optimal in carrying out the order.